The answer is the first option: Even.
The explanation for this exercise is shown below:
1. By definition, if
the fucntion is even.
2. When the graph is symmetric with respect to the y-axis, it is an even function.
3. As you you can see in the graph attached in the problem, the graph is symmetric about the y-axis. Therefore, you can conclude it is an even function.
Answer:
18x
Step-by-step explanation:
2(3x+6x)
Answer:
vertex = (0, -4)
equation of the parabola: ![y=3x^2-4](https://tex.z-dn.net/?f=y%3D3x%5E2-4)
Step-by-step explanation:
Given:
- y-intercept of parabola: -4
- parabola passes through points: (-2, 8) and (1, -1)
Vertex form of a parabola: ![y=a(x-h)^2+k](https://tex.z-dn.net/?f=y%3Da%28x-h%29%5E2%2Bk)
(where (h, k) is the vertex and
is some constant)
Substitute point (0, -4) into the equation:
![\begin{aligned}\textsf{At}\:(0,-4) \implies a(0-h)^2+k &=-4\\ah^2+k &=-4\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%5Ctextsf%7BAt%7D%5C%3A%280%2C-4%29%20%5Cimplies%20a%280-h%29%5E2%2Bk%20%26%3D-4%5C%5Cah%5E2%2Bk%20%26%3D-4%5Cend%7Baligned%7D)
Substitute point (-2, 8) and
into the equation:
![\begin{aligned}\textsf{At}\:(-2,8) \implies a(-2-h)^2+k &=8\\a(4+4h+h^2)+k &=8\\4a+4ah+ah^2+k &=8\\\implies 4a+4ah-4&=8\\4a(1+h)&=12\\a(1+h)&=3\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%5Ctextsf%7BAt%7D%5C%3A%28-2%2C8%29%20%5Cimplies%20a%28-2-h%29%5E2%2Bk%20%26%3D8%5C%5Ca%284%2B4h%2Bh%5E2%29%2Bk%20%26%3D8%5C%5C4a%2B4ah%2Bah%5E2%2Bk%20%26%3D8%5C%5C%5Cimplies%204a%2B4ah-4%26%3D8%5C%5C4a%281%2Bh%29%26%3D12%5C%5Ca%281%2Bh%29%26%3D3%5Cend%7Baligned%7D)
Substitute point (1, -1) and
into the equation:
![\begin{aligned}\textsf{At}\:(1.-1) \implies a(1-h)^2+k &=-1\\a(1-2h+h^2)+k &=-1\\a-2ah+ah^2+k &=-1\\\implies a-2ah-4&=-1\\a(1-2h)&=3\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%5Ctextsf%7BAt%7D%5C%3A%281.-1%29%20%5Cimplies%20a%281-h%29%5E2%2Bk%20%26%3D-1%5C%5Ca%281-2h%2Bh%5E2%29%2Bk%20%26%3D-1%5C%5Ca-2ah%2Bah%5E2%2Bk%20%26%3D-1%5C%5C%5Cimplies%20a-2ah-4%26%3D-1%5C%5Ca%281-2h%29%26%3D3%5Cend%7Baligned%7D)
Equate to find h:
![\begin{aligned}\implies a(1+h) &=a(1-2h)\\1+h &=1-2h\\3h &=0\\h &=0\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%5Cimplies%20a%281%2Bh%29%20%26%3Da%281-2h%29%5C%5C1%2Bh%20%26%3D1-2h%5C%5C3h%20%26%3D0%5C%5Ch%20%26%3D0%5Cend%7Baligned%7D)
Substitute found value of h into one of the equations to find a:
![\begin{aligned}\implies a(1+0) &=3\\a &=3\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%5Cimplies%20a%281%2B0%29%20%26%3D3%5C%5Ca%20%26%3D3%5Cend%7Baligned%7D)
Substitute found values of h and a to find k:
![\begin{aligned}\implies ah^2+k&=-4\\(3)(0)^2+k &=-4\\k &=-4\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%5Cimplies%20ah%5E2%2Bk%26%3D-4%5C%5C%283%29%280%29%5E2%2Bk%20%26%3D-4%5C%5Ck%20%26%3D-4%5Cend%7Baligned%7D)
Therefore, the equation of the parabola in vertex form is:
![\implies y=3(x-0)^2-4=3x^2-4](https://tex.z-dn.net/?f=%5Cimplies%20y%3D3%28x-0%29%5E2-4%3D3x%5E2-4)
So the vertex of the parabola is (0, -4)
Answer:
Two of those figures have a vertex.
Step-by-step explanation:
Hope this helped Mark BRAINLIEST!!!